Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Jasa Servis Sepeda Motor Honda Pada CV. Karisma Motor Samarinda. - yance mangalik; Suharno Suharno; Saida Zainurossalamaiah, ZA (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this research is to know the influence of the quality of service to customer satisfaction Services Service Honda Motorcycles On CV. Karisma Motor Samarinda. The research of using primary data in the form of a questionnaire. The data were analyzed by multiple linear regression models and using the computer programSPSS. Research and discussion of the results shows that the free Variables consisting of physical evidence, reliability, responsiveness, assurance, and empathy to simultaneously have significant influence towards variable customer satisfaction. Cv. Karisma Motor Samarinda. Results of research partially indicate that the variable guarantees and empathy who had a significant influence towards customer satisfaction CV. Karisma Motor Samarinda. Based on the results of the study it was found that the dominant effect of empathy towards customer satisfaction, because the value of t greatest compared variable physical evidence, guarantee, reliability, and responsiveness of CV.Â KarismaÂ MotorÂ SamarindaKeywords:Â Quality Of Service - Customer Satisfaction